Rationality, education and psychological suffering: COVID-19 pandemic as a time frame - Peres, Helga Caroline (2024)
This article considers the thesis discussed by T. W. Adorno and M. Horkheimer which the way of the modern rationality is an “introversion of sacrifice”. That thesis presupposes that the path of the historical development of civilization requires the deepening of human sacrifice as a price to pay. As it develops, the rationality itself poured into new control devices anchored in digital technologies engenders a new symptomatology. Anxiety, depression, fear, stress are symptoms that are increasingly manifested in large human contingents spread across different regions of the planet. In this sense, the Covid-19 pandemic, in its most critical period, 2020 – 2021, appears as a time frame from which these symptoms became, if not more explicit, at least more intense because of protective confinement measures.